2016
DOI: 10.21037/jtd.2016.04.67
|View full text |Cite
|
Sign up to set email alerts
|

Effect of small body habitus on peri-operative outcomes after robotic-assisted pulmonary lobectomy: retrospective analysis of 208 consecutive cases

Abstract: Patients with BSA ≤1.65 m(2) have similar perioperative outcomes and complication risks as patients with larger BSA. Patients with BSA ≤1.65 m(2) have a higher overall conversion rate to thoracotomy, but similar conversion rate for bleeding as patients with larger BSA. Robotic-assisted pulmonary lobectomy is feasible and safe in patients with small body habitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
1
9
1
Order By: Relevance
“…In an earlier cohort of 208 consecutive robotic-assisted lobectomies, Velez-Cubian et al suggested that small body habitus has the potential to increase the surgical difficulty and risk of perioperative complications because patients with a smaller BSA generally have smaller pleural cavities, which results in limited access to the operative field and poor thoracoscopic visualization. 19 Our present results, as well as those in our earlier study, seem contrary to this explanation; 6 however there is no evidence to explain these varying results. We suggest that the following two hypotheses may be considered for possible interpretations.…”
Section: Interpretationscontrasting
confidence: 99%
See 1 more Smart Citation
“…In an earlier cohort of 208 consecutive robotic-assisted lobectomies, Velez-Cubian et al suggested that small body habitus has the potential to increase the surgical difficulty and risk of perioperative complications because patients with a smaller BSA generally have smaller pleural cavities, which results in limited access to the operative field and poor thoracoscopic visualization. 19 Our present results, as well as those in our earlier study, seem contrary to this explanation; 6 however there is no evidence to explain these varying results. We suggest that the following two hypotheses may be considered for possible interpretations.…”
Section: Interpretationscontrasting
confidence: 99%
“…Velez‐Cubian et al . first reported the clinical significance of BSA in lung cancer surgery in a small cohort of 208 robotic‐assisted thoracoscopic lobectomy cases, but the association between BSA and risk of chylothorax remained unclear . In our earlier series of 442 patients undergoing VATS anatomical resections, we found that larger BSA was significantly associated with surgical procedure‐related complications but we did not investigate the impact of BSA on individual complications …”
Section: Introductionmentioning
confidence: 90%
“…Then, we further identified that BSA >1.73 m was a strongly independent predictor for conversion to thoracotomy in the multivariate logistic-regression model (OR: 7.17; P=0.028). Our results about the morbidity rates between two groups of BSA, showing no significant difference, were similar to what Velez Cubian et al (12) reported in their cohort.…”
Section: Interpretationssupporting
confidence: 92%
“…To our knowledge, there was only one retrospective analysis evaluating the effects of BSA on conversion to thoracotomy in 208 consecutive robotic-assisted lobectomies (12). The authors found that the patients with larger BSA had an obviously lower conversion rate than those with smaller BSA (P=0.030), although they did not conduct a multivariate analysis to further confirm the significance of BSA on serving as an independent risk factor.…”
Section: Interpretationsmentioning
confidence: 95%
See 1 more Smart Citation